Increasing the height of the anterior lip on a tibial insert in a posterior stabilized knee prosthesis has little effect on the wear rate. (May 2021) - Wang, Xiao-Hong; Bi, Zheng; Dong, Xiang; Hu, Sen-Yuan; Xu, Li-jun; Cheng, Cheng-Kung
Highlights: Knee implants with different anterior lip heights have a similar wear rate during different daily activities. The location of maximum wear depth was similar among the three tibial inserts tested with different lip heights. The tibial insert with the highest lip showed slight anterior wear scaring due to anterior contact during swing phase. Abstract: A high anterior lip on a total knee prosthesis is an effective way of reducing anterior translation, but the effect on joint wear is unclear. Using finite element analysis (FEA), this study quantitatively compared wear rates and anterior contact stresses in three posterior stabilized knee prostheses with different heights for the anterior lip during six daily activities (walking, stair ascent, stair descent, sit-to-stand, pivot turn and crossover turn). The wear rate and location of maximum wear depth were similar for the three lip heights tested, but the knee with the highest anterior lip also showed slight anterior wear scaring due to articular contact stress during swing phase, which was highly dependent on the shape of the contact interface. This study illustrates that tibial inserts with a high anterior lip maintain a wear rate similar to moderate and low lip posterior stabilized designs.